K63-Linked Polyubiquitination on TRAF6 Regulates LPS-Mediated MAPK Activation, Cytokine Production, and Bacterial Clearance in Toll-Like Receptor 7/8 Primed Murine Macrophages - Talreja, Jaya; Samavati, Lobelia (Frontiers in Immunology, 2018)
Post viral infection bacterial pneumonia is a major cause of morbidity and mortality associated with both seasonal and pandemic influenza virus illness. Despite much efforts put into the discovery of mechanisms of post viral bacterial infections and their complications in recent years, the molecular mechanisms underlying the increased susceptibility to bacterial infection remain poorly understood. In the present study, we focused on the pathways regulating immune responses in murine macrophages and modeled post viral bacterial infections through pretreatment of bone marrow derived macrophages (BMDMs) with a TLR7/8 ligand (R848) and subsequent challenge with TLR2/4 agonists to mimic bacterial infection. We found R848-primed BMDMs upon subsequent exposure to TLR2/4 ligands respond with enhanced inflammatory cytokine production, especially IL-6 and TNF-α. The enhanced cytokine production in R848-primed BMDMs in response to TLR2/4 was due to increased TAK1 phosphorylation with subsequent activation of ERK and p38 MAPKs. Furthermore, we identified that R848 priming leads to increased K63-linked polyubiquitination on TRAF6. K63-linked polyubiquitination on TRAF6 is a signal leading to enhanced activation of downstream pathways including TAK1. Importantly, R848-primed BMDMs infected with live bacteria exhibited decreased bacterial clearance. SMER3, an ubiquitin ligase inhibitor reversed the K63-linked polyubiquitination on TRAF6 in R848-primed BMDMs and subsequently decreased TAK1 and MAPK phosphorylation, and cytokine production as well as reversed the decreased bacterial clearance capacity of BMDMs. Our study may provide a novel molecular target to alleviate post viral bacterial infections.